Corticosteroid use is not associated with improved outcomes in acute exacerbation of IPF - Farrand, Erica; Vittinghoff, Eric; Ley, Brett; Butte, Atul J.; Collard, Harold R. (Respirology (Carlton, Vic.), 2020)
ABSTRACT Background and objective AE‐IPF has profound prognostic implications, preceding approximately half of all IPF‐related deaths. Despite this clinical significance, there are limited data to guide management decisions. Corticosteroids remain the mainstay of treatment despite a lack of strong supporting evidence and mounting concern that they may be harmful. We assessed the impact of corticosteroid therapy on in‐hospital mortality in AE‐IPF patients. Methods AE‐IPF subjects were retrospectively identified in the UCSF medical centre's electronic health records from 1 January 2010 to 1 August 2018 using a code‐based algorithm followed by case validation. The relationship between corticosteroid treatment and in‐hospital mortality was assessed using a Cox model and a propensity score to control for confounding by indication. Secondary outcomes included hospital readmissions and overall survival. Results In total, 82 AE‐IPF subjects were identified, of whom 37 patients (45%) received corticosteroids. AE‐IPF subjects treated with corticosteroids were more likely to require ICU level care and mechanical ventilation. There was no statistically significant association between corticosteroid treatment and in‐hospital mortality (propensity score weighted, adjusted HR: 1.31; 95% CI: 0.26–6.55; P = 0.74). Overall survival was reduced in AE‐IPF subjects receiving corticosteroids (HR: 6.17; 95% CI: 1.35–28.14; P = 0.019). Conclusion Our study found no evidence that corticosteroid use improves outcomes in IPF patients admitted to the hospital with acute exacerbation. Furthermore, corticosteroid use may contribute to reduced overall survival following an exacerbation. Observational cohort studies using larger real‐world cohorts can more definitively assess the relationship between corticosteroid treatment and short‐term outcomes in AE‐IPF. AE‐IPF are unpredictable and highly morbid events, for which corticosteroids have long been a recommended treatment. This study found no evidence that corticosteroids improve outcomes in patients with IPF hospitalized with an acute exacerbation and may contribute to reduced overall survival. See related Editorial